2008
DOI: 10.2967/jnumed.107.048538
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Biodistribution and Tumor Targeting of Two 99mTc-Labeled Anti-EGFR Nanobodies in Mice, Using Pinhole SPECT/Micro-CT

Abstract: Camelidae possess an unusual class of antibodies devoid of light chains. Nanobodies are intact antigen-binding fragments that are stable, easily generated against different targets, and fully functional. Their rapid clearance from the blood circulation favors their use as imaging agents. We compared the in vivo tumor uptake and biodistribution of 2 anti-epidermal growth factor receptor (anti-EGFR) Nanobodies, 99m Tc-7C12 and 99m Tc-7D12. Methods: Nanobodies were labeled via their hexahistidine tail with 99m Tc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
193
4
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 197 publications
(214 citation statements)
references
References 21 publications
(27 reference statements)
9
193
4
3
Order By: Relevance
“…This requires relatively hydrophilic molecules with a molecular size that is inferior to 60 kDa threshold for glomerular filtration. Nanobodies fit this description: they are hydrophilic, have a molecular size of 15 kDa, have a fast blood clearance and show low liver uptake (10). Together with their characteristic of specific targeting with affinities in the nanomolar range, they represent an interesting class of probes for the generic development of molecular imaging agents.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…This requires relatively hydrophilic molecules with a molecular size that is inferior to 60 kDa threshold for glomerular filtration. Nanobodies fit this description: they are hydrophilic, have a molecular size of 15 kDa, have a fast blood clearance and show low liver uptake (10). Together with their characteristic of specific targeting with affinities in the nanomolar range, they represent an interesting class of probes for the generic development of molecular imaging agents.…”
Section: Discussionmentioning
confidence: 96%
“…With the recent identification of a universal humanized nanobody scaffold, these probes are now also ready for clinical translation (8,9). In our previous work we identified 99m Tc-7C12 nanobody (Ablynx NV) as the lead compound for monitoring EGFR expression of cancer based on its high tumor uptake, fast blood clearance and low liver uptake (10,11). High-contrast images of EGFR-expressing lesions can be obtained as early as 1 h post injection (p.i.).…”
Section: Full Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Физико-химические свойства и небольшие размеры наноантител приводят к чрезвычайно быстрому распределению молекул по органам и тканям [47,121].…”
Section: наноантитела как диагностические препа ратыunclassified
“…Initial biodistribution studies with monospecific anti-EGFR (aEGFR)-Nanobodies in tumor-bearing mice showed, as expected, rapid blood clearance with a serum half-life time of less than an hour and low tumor uptake (15)(16)(17). Therefore, monospecific Nanobodies do not seem to be qualified for long-term blockage of growth factors and their receptors.…”
Section: Introductionmentioning
confidence: 99%